Escola e infância: processo de institucionalização dos jardins-de-infância na capital do Maranhão no período de 1870 até a década de 1930 - Morais, Rachel Tavares de (2018)
This research deals with the social process of institutionalization of nursery schools in the capital of the State of Maranhão (1870 to 1930). We start from the assumption that the appearance of nursery schools in the Maranhão scenario occurred as an element of social distinction in the school attendance of the child less than seven years of age, with phases marked by oppositions and tensions between social groups that had been occupying the field of early childhood education. This is a documentary and bibliographical research. Also, we examined non-pedagogical newspapers, such as Pacotilha, Diário de São Luís (The Daily of São Luís), O Combate (The Combat), O Jornal (The Newspaper), Notícias (The News), as well as pedagogical journals, laws, decrees, government messages. We also made use of publications by Maranhão authors in the field of education such as A Criança (The Child), (1909) and Questões da Educação (The Questions of Education), (1934). In the analysis and interpretation of the sources we sought to raise distinctive marks during the process of institutionalization of nursery schools that legitimized these establishments in the Maranhão educational scenario. The Nursery School Rosa and The Nursery School Decroly appear prominently in this research confirming the distinc tive social character due to involvement with social agents who were concerned with the educational issues of their time. Presenting the process of institutionalization of these establishments we hope to contribute to the history of education of Maranhão and to the school attendance for children less than seven years of age in the capital of the State of Maranhão.